Effect of processing parameters on the morphology, particulate, and superconducting properties of electrospun YBCO nanostructures - Jasim, Saleh Eesaa; Mohamad Ashry, Jusoh; Muhammad Aizat, Kamarudin; Fahmiruddin, Esa; Rodziah, Nazlan (Trans Tech Publications Ltd, 2020)
Superconductivity in nanostructured ceramics offers significant advantages over the conventional coarse-grained materials in view of miniaturization of superconducting electronic devices. In this paper, we report the formation of four morphologies of superconducting YBa2Cu3O7-δ (YBCO) nanostructures by electrospinning technique using polymeric polyvinyl pyrrolidone (PVP) solutions of different molecular weight and altering the total content of the metallic precursors. The morphologies prepared using this strategy are nanorods (NRs), nanogarlands (NGs), nanohierarchical (NH), and nanoparticles (NPs). Alternating current susceptibility measurements showed high critical temperatures (TC ~90 K) for the NH YBCO synthesized using PVP of the lowest molecular weight; whereas the YBCO NRs synthesized using a higher molecular weight polymer showed the lowest TC (82 K). A relationship between the particulate properties and TC was also observed – the lower is the pore size the higher is the TC. The YBCO NGs showed the highest specific surface area (7.06 m2/g) with intermediate TC (88 K). Electrospinning process appears an effective and controllable technique to produce different nanomorphologies with intrinsic properties suitable for practical applications.